A real-time monitoring instrument of induction machines for an integrated teaching test bench - Leite, V. (2003)
The purpose of this paper is to present a real-time analogue monitoring instrument developed for an integrated test bench for teaching as well as for R&D activities, in power electronics and variable speed drives of induction machines. The instrument is based on electronic modules and has been developed for monitoring the stator, rotor and magnetizing fluxes space phasors, electromagnetic torque as well as active and reactive powers.